Stimulatory Effect of 5-Hydroxytryptamine (5-HT) on Rat Capsaicin-Sensitive Lung Vagal Sensory Neurons via Activation of 5-HT3 Receptors - Hsu, Chun-Chun; Ruan, Ting; Lee, Lu-Yuan; Lin, You Shuei (Frontiers in Physiology, 2019)
5-hydroxytryptamine (5-HT) is an inflammatory mediator known to be released in lung. Capsaicin-sensitive lung vagal (CSLV) afferents function as a primary sensor for detecting chemical stimuli and produce consequent reflexes during lung inflammation. To characterize the effect of 5-HT on CSLV afferents, responses of cardiorespiratory reflexes and single-unit C-fiber afferents to right-atrial injections of 5-HT were investigated in anesthetized Sprague-Dawley rats. Bolus injection of 5-HT (8 μg/kg) caused an immediate augmented breath and apnea, accompanied by hypotension and bradycardia. These initial responses were then followed by a brief pressor response and a more sustained depressor response. After a perineural treatment of both cervical vagi with capsaicin to block the conduction of C fibers, 5-HT still triggered the augmented breath, but no longer evoked the apnea, bradycardia and hypotension, indicating an involvement of C-fiber activation. The remaining augmented breath induced by 5-HT after perineural capsaicin treatment was totally eliminated by vagotomy. To further study the effect of 5-HT on CSLV afferents, activities arising from these afferents were determined using the single-fiber recording technique. Right-atrial injection of 5-HT evoked an intense discharge in CSLV afferents in a dose-dependent manner. The highest dose of 5-HT (16 μg/kg) activated 79% (19/24) of CSLV afferents which were also sensitive to capsaicin (0.8 μg/kg). The pretreatment of tropisetron, a selective antagonist of the 5-HT3 receptor, completely blocked CSLV-afferents stimulation induced by 5-HT but did not affect that by capsaicin. Furthermore, a similar afferent response of CSLV afferents was mimicked by phenylbiguanide, a selective agonist of the 5-HT3 receptor. In isolated rat lung vagal C neurons, 5-HT induced intense calcium transients in a dose-dependent manner. The highest concentration (3 µM) of 5-HT activated 67% (18/27) of the CSLV neurons. The 5-HT-induced response was totally abolished by pretreatment of tropisetron. In conclusion, 5-HT exerts an intense stimulatory effect on lung C-fiber terminals mediated through an activation of the 5-HT3 receptor, which may contribute to the airway hypersensitivity under lung inflammation.